2022
DOI: 10.1111/jocn.16528
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses' experiences of physical restraint in intensive care units: A qualitative systematic review and meta‐synthesis

Abstract: Introduction Physical restraint is widely used in intensive care units. Critical care nurses are the primary decision makers and practitioners of physical restraint. However, little is known about the qualitative evidence of their experience of physical restraint. Aims To aggregate, synthesise and interpret the qualitative evidence of studies that explored critical care nurses' experiences of physical restraint in intensive care units. Methods A qualitative systematic review and meta‐synthesis was conducted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…One interesting result is that the courts’ decisions on the use of PR due to staff shortages (Ethical dilemma situation 2 and 3) were different. Staff shortages have been identified as a factor that drives the use of PR, regardless of the care recipient’s condition [ 51 , 52 ], and this is generally considered unethical situation, violating the principle of justice [ 16 , 36 ]. However, studies conducted in Iran have shown that in situations of staff shortage, staff suffer ethical distress because there is no alternative for patient safety other than PR [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting result is that the courts’ decisions on the use of PR due to staff shortages (Ethical dilemma situation 2 and 3) were different. Staff shortages have been identified as a factor that drives the use of PR, regardless of the care recipient’s condition [ 51 , 52 ], and this is generally considered unethical situation, violating the principle of justice [ 16 , 36 ]. However, studies conducted in Iran have shown that in situations of staff shortage, staff suffer ethical distress because there is no alternative for patient safety other than PR [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, even if PR is used with good intentions, it has a risk of causing physical and psychological damage [ 13 ] to care recipients, and it can sometimes be abused [ 14 ] for the convenience of health workers. In particular, nurses are the traditional PR decision-makers who are most involved in patient care [ 15 , 16 ], but fear of safety accidents, consequent criticism, and legal responsibility contribute to nurses’ use of PR [ 16 ], as does individual nurses’ poor ethical sensitivity [ 17 ]. All people have the right to equal freedom and dignity [ 18 ]; however, PR has long been controversial because it infringes on individuals’ freedom of movement, forcibly restricts autonomy, and has negative impacts on health workers, who experience guilt and ethical dilemmas [ 10 , 12 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] For ICU nurses, restraints confer a sense of security, but are also associated with feelings of guilt, sadness, and moral distress. 16,17 The 2018 Society of Critical Care Medicine Pain, Agitation/Sedation, Delirium, Immobility, and Sleep Disruption (PADIS) Clinical Practice Guidelines outline the many unintended and harmful consequences of physical restraint use, and recommend that efforts be taken to reduce their usage in the ICU setting. 18 As an alternative to traditional wrist restraints, a novel device, the Exersides ® Refraint ® (Healthy Design, Rutland, VT), was developed with the support of a National Institutes of Health Small Business Technology Transfer (STTR) Program Grant.…”
Section: Introductionmentioning
confidence: 99%
“…7 15 For ICU nurses, restraints confer a sense of security, but are also associated with feelings of guilt, sadness, and moral distress. 16,17 The 2018 Society of Critical Care Medicine Pain, Agitation/Sedation, Delirium, Immobility, and Sleep Disruption (PADIS) Clinical Practice Guidelines outline the many unintended and harmful consequences of physical restraint use, and recommend that efforts be taken to reduce their usage in the ICU setting. 18…”
Section: Introductionmentioning
confidence: 99%